(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Classical open vascular surgery remains the optimal treatment method for obliterating atherosclerosis of the arteries of the lower extremities. However, these interventions are associated with significant risks of perioperative complications and mortality. In modern surgery, there is a trend toward an increase in the number of endovascular interventions, which can reduce surgical trauma, reduce surgical time, and avoid anesthesia, which leads to a reduction in the risk of surgical complications. The purpose of our study was to study the effectiveness of treatment of patients with obliterating atherosclerosis against the background of diabetes mellitus. In clinical practice, the method of surgical treatment using angiographic examination, taking into account the 3rd level of the size of the vessels of the foot, is to carry out endovascular intervention using minimally invasive methods of recanalization, balloon angioplasty and stenting of distal vessels.